Relationships between student engagement in higher education and academic success and desire to attend university - Bilir Koca, Burcu; Karadağ, Engin (Journal of International Students, 2025)
The purpose of this research is to examine the relationships between student engagement in a higher education system and the desire to attend university and academic success. A causal design was used in the research. The research sample consisted of 3,093 undergraduate students in Turkey, selected using the stratified sampling method. NSSE was used as a data collection tool in the study. Pearson product-moment correlation analysis, simple linear regression analysis, and multilevel logistic regression analysis were used to analyze the data. Within the scope of the research, it was determined that student engagement statistically significantly predicted academic success and the desire to attend university. As students’ level of engagement increases, their academic success and desire to attend their universities also increase. In this context, universities should establish institutional policies to enhance student engagement and regularly evaluate their progress by measuring the level of student engagement within their institutions.